Comparison of the Effectiveness of Intensive Short-Term Dynamic Psychotherapy (ISTDP) and Transference-Focused Psychotherapy (TFP) on Impulsivity and Cognitive Emotion Regulation in Patients with Borderline Personality Disorder - Gholami Mazinan, Siamak; Hashemi, Sara; Jomehri, Farhad (Psychology of Woman Journal, 2026)
Objective: The present study aimed to compare the effectiveness of Intensive Short-Term Dynamic Psychotherapy (ISTDP) and Transference-Focused Psychotherapy (TFP) on impulsivity and cognitive emotion regulation in patients diagnosed with Borderline Personality Disorder.Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest control group and a three-month follow-up phase. The statistical population consisted of female patients diagnosed with Borderline Personality Disorder who were referred to psychiatric and psychological clinics in District 3 of Tehran during the first quarter of 2026. Forty-five participants were selected using purposive sampling and randomly assigned into three groups, including ISTDP, TFP, and a control group. The research instruments included the Cognitive Emotion Regulation Questionnaire (CERQ) and the Barratt Impulsiveness Scale (BIS-11), which were administered at the pretest, posttest, and follow-up stages. The TFP intervention was implemented in twelve weekly 60-minute sessions, whereas the ISTDP intervention was conducted in ten weekly 60-minute sessions. Data were analyzed using repeated-measures multivariate analysis of variance in IBM SPSS Statistics Version 26.Findings: The findings demonstrated that both ISTDP and TFP significantly reduced impulsivity and improved cognitive emotion regulation compared to the control group (p < 0.001). Significant interaction effects between time and group membership were observed for non-planning impulsivity and cognitive impulsivity, while no significant interaction effect was found for motor impulsivity. Moreover, significant improvements were observed in most components of cognitive emotion regulation, including self-blame, rumination, positive refocusing, planning-focused refocusing, positive reappraisal, and perspective taking. Bonferroni post-hoc comparisons indicated that TFP was more effective than ISTDP in improving adaptive cognitive emotion regulation strategies and reducing cognitive dimensions of impulsivity. The treatment effects remained relatively stable during the three-month follow-up period.Conclusion: The findings suggest that both Intensive Short-Term Dynamic Psychotherapy and Transference-Focused Psychotherapy are effective interventions for reducing impulsivity and improving cognitive emotion regulation in patients with Borderline Personality Disorder. However, TFP demonstrated superior effectiveness in enhancing reflective and cognitive aspects of emotional regulation. These results highlight the importance of psychodynamic interventions that focus on emotional processing, personality organization, and reflective functioning in the treatment of Borderline Personality Disorder.